40. MANAGEMENT OF PERSISTENT AIR LEAK AFTER THORACOSCOPIC LOBECTOMY FOR NON-SMALL CELL LUNG CANCER AT THE NATIONAL LUNG HOSPITAL: PREDICTION, PREVENTION AND TREATMENT (Vietnam Journal of Community Medicine, 2024)
Background: Prolonged air leak (PAL) after thoracoscopic lobectomy for non-small cell cancer (VATS) is a common complication. We explored pre-intervention prognostic risk factors and evaluated whether quantitative measurement of intraoperative air leak using mechanical ventilation testing can predict, prevention, management PAL and identify patients requiring additional treatment.Methods: 84 patients underwent thoracoscopic cancer lobectomy (VATS) from April 2023 - December 2023 at the National Lung Hospital. Research by descriptive and retrospective method.Results: At the end of the lobectomy, the remaining lung lobe was immersed in re-inflated ventilation water with a pressure of 25-30 cmH2O to evaluate the air leak situation, and have a treatment strategy to limit the PAL condition. prolongation after surgery and post-operative management directions.Conclusion: Preoperative and intraoperative risk factors using mechanical ventilation test help evaluate PAL after VATS lobectomy, thereby providing appropriate intraoperative and postoperative management for patients to withdraw drainage and discharge early, limiting possible complications when draining the pleural space for a long time in patients.
Keywords: Prolonged air leak (PAL).